The Cellular Response to Protein Misfolding in the Endoplasmic Reticulum - Welihinda, Ajith A. (Gene Expr, 2018)
In eukaryotic cells, accumulation of unfolded proteins in the lumen of the endoplasmic reticulum (ER) leads to a stress response. Cells respond to ER stress by upregulating the synthesis of ER resident protein chaperones, thus increasing the folding capacity in this organelle. In addition, this response also activates pathways to induce programmed cell death. The stress-induced chaperone synthesis is regulated at the level of transcription. In Saccharomyces cerevisiae, the transmembrane protein, Ire1p, with both serine/threonine kinase and site-specific endoribonuclease activities is implicated as the sensor of unfolded proteins in the ER that transmits the signal from the ER to activate transcription in the nucleus. Activation of the unfolded protein response (UPR) pathway also requires the bZIP transcription factor, Hac1p. Although HAC1 is transcribed constitutively, the mRNA is poorly translated. Upon accumulation of unfolded proteins, Ire1p generates a new processed form of HAC1 mRNA that is efficiently translated by removal of a 252 base sequence. Using the yeast-interaction trap system we identified additional components of the UPR. A yeast transcriptional coactivator complex, Gcn5p/Ada, which is composed of Gcn5p, Ada2p, Ada3p, and Ada5p, was identified that interacts with Ire1p and Hac1p. Deletion of GCN5, ADA2, and/or ADA3 reduces, and deletion of ADA5 completely abrogates, the transcriptional induction in response to misfolded protein in the ER. A protein phosphatase, Ptc2p, was also identified as a negative regulator of the UPR that directly interacts with and dephosphorylates activated Ire1p. Recently, two mammalian homologues of Ire1p, IRE1 and IRE2, were identified, hlrelp, is preferentially localized to the nuclear envelope and requires a functional nuclease activity to transmit the UPR. These results indicate that some features of the UPR are conserved from yeast to humans and may be composed of a multicomponent complex that is regulated by phosphorylation status and is associated with the nuclear envelope to regulate processes including transcriptional induction and mRNA processing. We propose that activation of Ire1p induces splicing of HAC1 mRNA as well as engages and targets the Gcn5/Ada/Hac1 protein complex to genes that are transcriptionally activated in response to unfolded protein in the ER. The transcriptional activation is facilitated by targeting the histone acetylase, Gcn5p in yeast, to promote histone acetylation at chromatin encoding ER stress-responsive genes. In addition, activation of Ire1p leads to increased lipid biosynthesis, thereby allowing ER expansion to accommodate increasing lumenal constituents. Under conditions of more severe stress, cells activate an Ire1p-dependent death pathway that is mediated through induction of GADD153/CHOP.